Reforming the system of legislative regulation of the activities of private employment agencies in the field of labor intermediation in Kazakhstan - Khassenov, M. Kh. (Bulletin of the Karaganda University “Law Series”, 2024)
This article presents the results of a study of the legal basis of the activity of private employment agencies (PEAs) in Kazakhstan and several foreign states. The purpose of this article is to improve the regulatory framework for the provision of employment services by private business entities, taking into account the rights and legitimate interests of citizens and migrants. On the basis of methods of analogy, legal modeling, formal-legal and comparative-legal methods, the necessity of reforming the system of regulation of labor intermediation implemented by PEAs has been scientifically substantiated. The author analyzed the statistical data of the market of employment services in Kazakhstan, revealing the shortcomings associated with the lack of proper regulation and control over the activity of PEAs. In Kazakhstan, a liberal model of regulation of the activity of providing services in the field of employment mediation has been developed. This model does not comply with international labor standards and standards of recruitment integrity system, it creates numerous risks associated with labor exploitation and other violations of human rights. In addition, the relevant norms are fragmentary, there is no full-fledged legal structure that determines the order of interaction of PEAs with job-seekers, state bodies and employers. In this regard, the development and adoption of the Law of the Republic of Kazakhstan «On Private Employment Agencies» is justified. Gaps in the regulatory policy make it necessary to introduce a permit-licensing procedure for the regulation of employment services with the mandatory availability of authorized capital, qualified personnel and material resources at PEAs to ensure the fulfillment of obligations to job seekers.